Determinants of Household Decision to Join Community Forest Associations: A Case Study of Kenya. (10th January 2013) - Musyoki, Josephine Kamene; Mugwe, Jayne; Mutundu, Kennedy; Muchiri, Mbae
Abstract : Forests contribute significantly to the livelihoods of forest adjacent communities. Under the Kenya's new Forest Act (2005), community participation in forest conservation is provided for through formation of Community Forest Associations (CFAs). This study focused on Ontukigo and Ngare Ndare CFAs involved in participatory management of Ontulili and Ngare Ndare forests in North Central Kenya. It aimed at identifying household factors associated with decision to participate in PFM and the differences between CFA and non-CFA members in their participation in forest conservation activities. Semi structured questionnaires were administered to randomly selected 80 CFA and 80 non-CFA members. Factors influencing household decision to join CFA included household size (t = 2.065, P = 0.05 ), age (t = 2.408, P = 0.01 ), number of cows (t = 2.804, P = 0.01 ) and sheep (t = 1.656, P = 0.01 ) owned by CFA (6.6) and non-CFA (4.2), farm size (t = 1.495, P = 0.01 ) and forms of land tenure. Other factors included distance of homestead from forest (t = − 1.253, P = 0.05 ), sources of fodder (χ 2 = 20.277, P = 0.001 ), access to forest products (χ 2 = 15.882, P = 0.001 ), crop land (χ 2 = 22.762, P = 0.001 ), and awareness of Forest Act 2005 (χ 2 = 22.227, P = 0.001 ). Participation in forest conservation was positively influenced by CFA membership (χ 2 = 7.83, P = 0.05 ). Majority of CFA members (80%) participated highly in forest patrol, fire control, tree nurseries, and tree planting activities.